Jadwiga Puzynina jako badaczka języka autorów - Kozłowska, Anna (Idiolekty, 2026)
This article characterises the scholarly output of Jadwiga Puzynina as a researcher of authors’ language. As her studies of Norwid have already been discussed elsewhere, the article concen trates on her research devoted to other writers, including Zbigniew Herbert, Jan Kochanowski, Wojciech Kudyba, Stanisław Jerzy Lec, Czesław Miłosz, Janusz St. Pasierb, Jan Twardowski, and Karol Wojtyła, as well as on her works on the theoretical issues involved in the descrip tion of idiolects. The article is supplemented with a bibliography of Jadwiga Puzynina’s pub lications on the language of authors.